Ação de fitorreguladores na qualidade pós-colheita de flores de corte de antúrio (Anthurium andraeanum L.) Cv. Arizona - DINIZ, Nathália Bandeira (2016)
The physiology and conservation of cut flowers, can be changed by the application of growth regulators such as gibberellins and polyamines. It is evident that both alone increased the shelf life of flowers, demonstrating the variability in responses to growth regulators flowers. However, studies with the combination of gibberellic acid (GA3) and polyamines (PAs) in tropical flowers are scarce. Thus the aim of this study was to evaluate the effect of gibberellic acid and Spermine (SPM) in physiology and conservation of anthurium flowers cv. Arizona. The rods Anthurium were harvested, transported, and selected immerged bases as well as their espádices sprayed. The pulsing or spray solution containing 144 μM GA3, Spm 2 μM and 144 μM GA3 Spm + 2 μM. The control corresponded to immersion or spraying in distilled water. After 24 hours, the solutions were replaced with distilled water, changed every 3 days. Samples of the stems and the spadix were collected every three days, and subjected to analysis: visual quality; fresh pasta; electrolyte leakage; total soluble protein; soluble carbohydrates; polyamines (Putescina, Spermine, Spermidine, Cadaverine Serotonin, Histamine, Tyramine and Dopamine); total phenolic compounds; enzymes were extracted and quantified superoxide dismutase, polyphenol oxidase and peroxidase. The experimental design was completely randomized in a factorial design, consisting of two application methods (pulsing and spraying) four concentrations of Gibberellic Acid and Spermine. The graphics were generated using the media and the deviations with software aid Sigma Plot version 12. The significant increase conservation is associated with lower physical and chemical changes, represented by fresh mass, electrolyte leakage, soluble phenols, higher levels Putrescine, Spermine, Spermidine and Cadaverine and serotonin, stability and total soluble proteins, and smaller increase in the activities of PPO, POD and SOD. Thus, spraying with GA3 and SPM combination at concentrations 144 μM and 2μM respectively folded storage time of 6 to 12 days. While pulsing 6 to 9 days of anthurium flowers cv. Arizona demonstrating that the application of direct plant growth regulators in bloom was more effective relative to solution in which the bases were submerged in the storage of flowers, since the spray have less barriers as well as smaller distance to the flower cells, may the regulators tested hit the target more efficiently.